Proceedings of the 23rd International Electronic Conference on Synthetic Organic Chemistry 2019
DOI: 10.3390/ecsoc-23-06502
|View full text |Cite
|
Sign up to set email alerts
|

VALIDATED STABILITY- INDICATING HPTLC METHOD FOR NINTEDANIB & CHARACTERIZATION OF DEGRADANTS BY LC-MS<sup>n</sup>

Abstract: A simple and rapid stability-indicating method for determination of nintedanib (NTB) in bulk drug using HPTLC and LC-MS n was developed and validated. Stress degradation studies were carried out by hydrolysis, oxidation, thermal and photolytic. Drug was found to be stable in thermal whereas one degradant was found in acid hydrolysis, three in basic hydrolysis, five in oxidative and two in photolytic stress. The probable structures of the degradation products were predicted & the degradation pathway was also es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…5 Pasquini et al have reported a quality by design (QbD) based LC-MS method for estimating NTB and its impurities in soft gelatin capsules. 6 Several investigators have reported various methods like RP-UPLC, 7 LC-MS, 8 RP-HPLC in formulation, and determination of NTB and its stress degradation, 9 and which help in estimating the NTB. Some of the methods also reported degradation pathways and the degradation nature of NTB in various solvents with time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Pasquini et al have reported a quality by design (QbD) based LC-MS method for estimating NTB and its impurities in soft gelatin capsules. 6 Several investigators have reported various methods like RP-UPLC, 7 LC-MS, 8 RP-HPLC in formulation, and determination of NTB and its stress degradation, 9 and which help in estimating the NTB. Some of the methods also reported degradation pathways and the degradation nature of NTB in various solvents with time.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 The method is precise, rapid, simple and accurate to estimate NTB as per ICH Q2 (R1) guidelines. 8 The developed method is used to quantify NTB in Nanostructured lipid carriers (NLCs) loaded with NTB. NLCs are the modified form of solid lipid nanoparticles.…”
Section: Introductionmentioning
confidence: 99%